Impact of soil depth and topography on the effectiveness of conservation practices on discharge and soil loss in the Ethiopian Highlands - Akal, Adugnaw T.; Dagnew, D.C.; Belete, M.A.; Tilahun, Seifu A.; Mekuria, Wolde; Steenhuis, Tammo S. (MDPI, 2017)
Restoration of degraded landscapes through the implementation of soil and water conservation practices is considered a viable option to increase agricultural production by enhancing ecosystems. However, in the humid Ethiopian highlands, little information is available on the impact of conservation practices despite wide scale implementation. The objective of this research was to document the effect of conservation practices on discharge and sediment concentration and load in watersheds that have different soil depths and topography. Precipitation, discharge, and sediment concentration were measured from 2010 to 2012 in two watersheds in close proximity and located in the Lake Tana basin, Ethiopia: Tikur-Wuha and Guale watersheds. The Tikur-Wuha watershed has deep soils and a gentle slope stream channel. The Guale watershed has shallow soils and a steep slope stream channel. In early 2011, the local community installed upland conservation measures consisting of stone and soil bunds, waterways, cutoff drains, infiltration furrows, gully rehabilitation, and enclosures. The results show that conservation practices marginally decreased direct runoff in both watersheds and increased base flow in the Tikur-Wuha watershed. Average sediment concentration decreased by 81% in Tikur-Wuha and 45% in Guale. The practices intended to increase infiltration were most effective in the Tikur-Wuha watershed because the deep soil could store the infiltrated water and release it over a longer period of time after the rainy season than the steeper Guale watershed with shallow soils.